2019
DOI: 10.3389/fpubh.2019.00295
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Post-partum Depression Risk Factors: The Role of Socio-Demographic, Individual, Relational, and Delivery Characteristics

Abstract: Postpartum depression is a common and complex phenomenon that can cause relevant negative outcomes for children, women and families. Existing literature highlights a wide range of risk factors. The main focus of this paper is to jointly investigate different types of risk factors (socio-demographic, psychopathological, relational, and related to labor and birth experience) in post-partum depression onset in women during first-child pregnancy, identifying which of these are the most important predictors. A coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 65 publications
(81 reference statements)
4
82
3
3
Order By: Relevance
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were mainly conducted in the US (10 papers) [80,[84][85][86][87][88][89][90][91][92] and in Europe (nine papers in Italy [93][94][95][96][97][98][99][100][101], four in Sweden [76,[102][103][104], two in Germany [105,106], one in the Netherlands [22], one in France [107], one in England [79], one in Belgium [108], and one in Portugal [75]). Four studies were carried out in Japan [81,[109][110][111], two in Australia [112,113], two in Iran [74,114], two in Turkey [78,115], one in India [116], one in Israel [117], one in Chile [118], one in Brazil [119], and one in Korea [120] (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies [76,[78][79][80]85,87,93,96,100,103,109,113] did not observe significant results. Ten papers reported that lower levels of prenatal attachment were associated with higher postnatal depression scores [74,81,95,99,101,105,110,111,116,117]; however, one study [85] did not support the association between these two variables. Four studies analyzed the influence between partner's depressive symptoms and own prenatal attachment [75,87,97,102].…”
Section: Main Findingsmentioning
confidence: 98%
See 3 more Smart Citations